2000
DOI: 10.1093/jhered/91.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of the tamaraw Bubalus mindorensis): a comparison of R-banded karyotype and chromosomal distribution of centromeric satellite DNAs, telomeric sequence, and 18S-28S rRNA genes with domestic water buffaloes

Abstract: The karyotype of the tamaraw (Bubalus mindorensis, 2n = 46) was investigated by RBG-banding technique and compared with those of the river and the swamp cytotypes of domestic water buffalo (B. bubalis). The tamaraw karyotype consisted of 6 submetacentric and 16 acrocentric autosome pairs (NAA = 56), and X and Y chromosomes. The RBG-banded karyotype of the three taxa had a high degree of homology, and the tamaraw karyotype could be explained by a Robertsonian translocation between chromosomes 7 and 15 and by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…8 c, d). The intensity of hybridization signals was constant and each chromosome generally exhibited four signals confirming the telomeric pattern previously found in most bovid species (Meyne et al, 1990;de la Seña et al, 1995;Tanaka et al, 2000).…”
Section: Fish Analysissupporting
confidence: 86%
See 2 more Smart Citations
“…8 c, d). The intensity of hybridization signals was constant and each chromosome generally exhibited four signals confirming the telomeric pattern previously found in most bovid species (Meyne et al, 1990;de la Seña et al, 1995;Tanaka et al, 2000).…”
Section: Fish Analysissupporting
confidence: 86%
“…However, Tanaka et al's interpretation is likely erroneous since the same chromosome was matched twiceonce as chromosome R6, and then as chromosome R12 of river buffalo; in the latter case it was presumably homologous to the tamaraw's chromosome 1q ( Fig. 3 in Tanaka et al, 2000). Similar errors occur elsewhere in their comparison and it seems that this disagreement results from a partial lack of correspondence in chromosome numbering using G-and R-banded chromosome nomenclature, and the mismatching of at least two chromosomal pairs in the Tanaka et al (2000) publication.…”
Section: Chromosomal Changes In Evolution Of the Family Bovidaementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the (T 2 AG 3 ) n sequence is retained during fusion events in some species (Lee et al, 1993;Thomsen et al, 1996;Vermeesch et al, 1996;Fagundes et al, 1997;Fagundes and Yonenaga-Yassuda, 1998), but not others (Schubert et al, 1992;Garagna et al, 1995;Nanda et al, 1995;Thomsen et al, 1996;Tanaka et al, 2000). For both the 6ˆ10 fusion of P. l. hacketti and the 9ˆ10 fusion of the West Kimberley race, (T 2 AG 3 ) n sequence signals were identified near the centromere, the presumed site of fusion (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…In Bubalus mindorensis (tamaraw) (2n = 46, FN = 56) there are 6 biarmed chromosomes resulting from centric fusions, 5 of which are identical to the swamp buffalo, plus one additional translocation, the 4; 14 [Tanaka et al, 2000a]. Most likely, the mindorensis is a recent derivation from the swamp buffalo.…”
Section: Centric Fusion Translocationsmentioning
confidence: 99%